Thoracic spinal anaesthesia – An effective alternative to general anaesthesia in breast surgeries: A randomised, non-blinded study - G S Karthik; Rangalakshmi Srinivasan; R Sudheer; M Amabareesha; T S Monisha; M Dilip Kumar (Indian Journal of Anaesthesia)
Background and Aims: General anaesthesia (GA) is the preferred modality for breast surgeries; however, neuraxial anaesthesia can be performed in cases where GA poses a significant risk. We hypothesise that neuraxial blockade is a safe and effective alternative to GA in short-duration breast surgeries. Methods: This randomised study included 30 patients of the American Society of Anesthesiologists physical status I and II, who were scheduled for elective breast surgeries of a duration of less than 90 min. Group I received thoracic spinal anaesthesia, while in Group II, standardised GA was administered. The primary outcome was the time to the first rescue analgesic, and the secondary outcomes were time to recovery, patient satisfaction and the cost incurred. Results: The demographic characteristics of both groups were comparable (P > 0.05). The time to first rescue analgesic in Group I was more than in Group II (P = 0.001). Patient satisfaction score was superior in Group I compared to Group II (P = 0.002). The average cost was lower in Group I compared to Group II (P = 0.002). Recovery was quicker in Group I than in Group II (P = 0.001). There were no significant haemodynamic disturbances or major complications in either group. Conclusion: Thoracic spinal anaesthesia is an excellent alternative to GA in terms of analgesic efficacy, patient satisfaction, recovery and cost-effectiveness for short-duration breast surgeries.